Airport revenue management: does airport size matter? - Chin, Anthony T. H.; Ong, Derek Lai Teik * (2014)
Airports today operate as business entities. Competition between airlines has revolutionized the way airports operate. There is an increasing preference for smaller airports. This has improved the economic and financial viability of small and medium airports from non-aeronautical revenue. An empirical study examines the relationship between airport size and airport profits. There is no statistically significant evidence from the results to suggest that small/medium airports are less profitable than major hub airports as the former reconfigure their activities in response to changing circumstances.